Intracameral vent and flush technique for silicone oil blockade in Ahmed glaucoma valve - Vaibhav Namdev; Arnav Panigrahi; Monika Arora; Viney Gupta; Shikha Gupta (Indian Journal of Ophthalmology, 2022)
The presence of emulsified silicone oil in the eye can lead to many complications, glaucoma being one of the most common. Adequate IOP control is difficult to achieve with medical management alone; surgical intervention is often required. Glaucoma drainage device implantation is often the preferred line of surgical intervention in such cases due to trabeculectomy failure from emulsified silicone oil droplets and associated conjunctival scarring. However, the silicone tube of Ahmed glaucoma valve (AGV) may attract the silicone oil droplets, causing blockade of the tube with persistent raised IOP postoperatively. We report one such case where post-AGV silicone oil tube occlusion was treated with semi-conservative surgical management instead of revising the entire surgery or implantation of another drainage device. Our surgical technique of intracameral “vent and flush” offers rapid and effective IOP control in such cases. Postoperatively, normal IOP was achieved. Patency of tube continued to be maintained along with normalization of IOP on subsequent follow-ups.